2020
DOI: 10.1002/app.50047
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of hydrophobicity of natural rubber latex films using diatomaceous earth

Abstract: Enhancement of the hydrophobic nature of natural rubber latex (NRL) films will open up a wide range of applications for them. Incorporating hexadecyltrimethoxysilane treated superhydrophobic diatomaceous earth (DE) in NRL, resulted in films with increased hydrophobicity. The nano‐scale surface roughness for the superhydrophobic surface was provided by DE and low surface energy was achieved by treating DE with hexadecyltrimethoxysilane (treated DE). Surface wettability and morphology were analyzed by water cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…WCA values categorized the wettability of the surface of coatings. The surfaces with WCA values >90° are considered hydrophobic, while WCA values >150° are superhydrophobic . The WCA measurements of the NR-based coatings produced from chloroform (CHF) and toluene (TOL) presented values of 94.3 and 93.1°, respectively (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…WCA values categorized the wettability of the surface of coatings. The surfaces with WCA values >90° are considered hydrophobic, while WCA values >150° are superhydrophobic . The WCA measurements of the NR-based coatings produced from chloroform (CHF) and toluene (TOL) presented values of 94.3 and 93.1°, respectively (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies also found it useful for improving the excellent electromagnetic interference (EMI) properties of rubber composites. , Thus, MoS 2 emerged as a material of interest and was used in the present study. The other material of interest used as a filler in rubber composites in the present work is D.E . Alam et al show that D.E.…”
Section: Introductionmentioning
confidence: 87%
“…The other material of interest used as a filler in rubber composites in the present work is D.E. 25 Alam et al 26 show that D.E. contains various functional groups on its outer and inner octahedral sheets and leads to robust interfacial interactions in the composite.…”
Section: ■ Introductionmentioning
confidence: 94%
“…This fact may hinder the production of NRL and NR devices suitable for biomedical purposes since the polymer chains limit the manufacturing of high-porous biomaterials. Although NRL is inherently hydrophilic, after the drying process, it becomes predominantly hydrophobic [101] . For biomedical applications, a surface with hydrophilic property is needed for adhesion, dissemination, and cell proliferation [102] .…”
Section: Comparison With Other Biopolymersmentioning
confidence: 99%